2005
DOI: 10.1143/jpsj.74.2703
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Scaling of an Adsorption–Diffusion Process on Fractals

Abstract: We study numerically a dynamic scaling of a diffusion process involving the Langmuir type adsorption. We find dynamic scaling functions in one and two dimensions and compare them with direct numerical simulations. We study further the dynamic scaling law on fractal surfaces. The adsorption-diffusion process obeys the fracton dynamics on the fractal surfaces.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Such approaches do not consider long-term correlations and long-range interactions appearing in diffusion processes occurring on complex domains such as self-similar (or fractal) structures. The work of Sakaguchi (2005) incorporates anomalous diffusion concepts into the analysis of adsorption-diffusion dynamics on fractal objects. Through direct simulations, Sakaguchi found that the adsorbed quantity followed a power-law time-dependent diffusion coefficient, i.e., In this work, we developed a pore volume and surface diffusion model that incorporates anomalous diffusion features, with the difference from previous works being that our proposal is based on the fractal continuum approach that considers the fractality in the adsorbate geometrical characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Such approaches do not consider long-term correlations and long-range interactions appearing in diffusion processes occurring on complex domains such as self-similar (or fractal) structures. The work of Sakaguchi (2005) incorporates anomalous diffusion concepts into the analysis of adsorption-diffusion dynamics on fractal objects. Through direct simulations, Sakaguchi found that the adsorbed quantity followed a power-law time-dependent diffusion coefficient, i.e., In this work, we developed a pore volume and surface diffusion model that incorporates anomalous diffusion features, with the difference from previous works being that our proposal is based on the fractal continuum approach that considers the fractality in the adsorbate geometrical characteristics.…”
Section: Introductionmentioning
confidence: 99%